AN INVESTIGATION OF QUALITY OF LIFE RELATED TO PROSTHESIS IN SYRIAN REFUGEE LOWER EXTREMITY AMPUTEES - TATAR, YAŞAR (TURKEY ASSOC PHYSIOTHERAPISTS, 2020)
Purpose: The use of prosthesis and an individual's perception of the prosthesis are associated with the quality of life. The study aimed to evaluate the quality of life related to prosthesis in Syrian refugees with lower extremity amputees. Methods: The study was conducted at three different prosthetic-orthotic centers managed by the Alliance of International Doctors. Seventy-six male (age=37.76 +/- 12.83 years) and 12 females (age=37.16 +/- 16.07 years) Syrian refugees with unilateral lower extremity (transtibial and transfemoral/knee disarticulation) amputation were evaluated. Demographic and amputation and prostheses-related characteristics were recorded. Quality of life related to the prosthesis was evaluated using the Prosthetic Evaluation Questionnaire (PEQ). Results: All PEQ scores of the transtibial and transfemoral/knee disarticulation amputees were similar (p>0.05). The PEQ-Appearance score of the single amputees was observed to be significantly lower than the married amputees (p=0.013). The PEQ-Ambulation score of participants using prosthesis over one year was significantly higher (p=0.038). The PEQ-Sound score of participants using prosthesis less than one year was found significantly higher (p=0.048). The PEQ-sound scores of chronic disease group were significantly higher than those of accident and war associated amputees (p=0.020). Conclusion: Quality of life of the refugee amputees regarding prosthesis and living with a prosthesis were similar regardless of the level of amputation. Expectations change with the increase in the duration of prosthesis use, and in single amputees, the expectation of cosmetic appearance becomes a concern.
Keywords: Amputees; Prosthesis; Quality of Life; LOWER-LIMB AMPUTATION; EVALUATION QUESTIONNAIRE; MOBILITY; SATISFACTION; INDIVIDUALS; EXPERIENCE; SOCKET